Prototype Home Automation based on Cloud Server - Rahmanto, Randy; Widodo, Sulistyo; Ayuningtyas, Belinda (Andhara, 2022)
Internet of things is a concept in which an object or object is implanted with technologies such as sensors and software with the aim of communicating, controlling, connecting, and exchanging data through other devices as long as they are connected to the internet. One way to connect the devices (in this research is Arduino microcontroller) is using a Web API. This technology is designed as a medium for data exchange between the Microcontroller and the Server. With this Web API it is possible to store data and control devices from the cloud server. In this research, a simple device is made using an Arduino microcontroller with a temperature sensor that will send data to the Web API, so that the data can be stored in a database on the cloud server. In addition, there are also LED lights that can be controlled from anywhere as long as there is an internet connection. The benefits of this research, with the use of Web APIs, allow users to be able to monitor and control IoT devices from anywhere as long as the device and user are connected to the internet.